Information Support for the Statistical Assessment of Labor Market Demand in Ukraine - L. H. Tkachenko (Статистика України, 2021)
The statistical assessment of labor market demand has to focus on qualitative rather than quantitative characteristics of jobs from the perspective of opportunities for choice and development of employed. Such assessment of jobs requires information and technical support. A review of the available information sources on the number and structure of jobs lays the ground for constructing a comprehensive assessment methodology on the basis of official statistical observations supplemented by administrative data on vacancies. It is shown that each source has its strong and weak sides. The strong sides of official sources are systemic professional approach and standardized techniques for data collection and processing, regularity, data quality control and accountability. But these sources still remain hardly accessible for research purposes, their data are compiled by the formal and sectoral approach and published in highly aggregated form. Alternative sources, including independent analytical and marketing studies, online databases of vacancies, are displayed in open access and contain detailed vacancy descriptions. But these data are unstructured, fragmented and need careful treatment due to a high probability of the system bias caused by broad applications of marketing strategies.